(3GdLGeY GdUMjMs - (3eMeO Hf YjSi Hf ShQI Hf ehSi GdSdej GdHhZj GdJQePj, CHh YjSi ,J (B279 (3g` s ((3YHOGdQMef Hf eMeO Hf Ydj GHf EHQGgje GdEQHdj s)
(3ChdgG (B:s
(3jHJOF HHGH eG LGA ai WdGbI GdhLg hMSf GdHTQ s
(3Ydi gPG GdLRA SeGYGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B104 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B519s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B75 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B559s
Keywords: (3GdMOjK h GdeUWdMs